2002
DOI: 10.5713/ajas.2002.1738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraruminal Saliva Flow on Feed Intake in Goats Fed on Alfalfa Hay Cubes

Abstract: Research was carried out to ascertain whether or not the volume of saliva flowing into the rumen regulates dry forage intake in ruminants. Goats with a parotid fistula were fed roughly crushed alfalfa hay cubes, concentrated beef cattle feed and NaHCO 3 twice daily (10:00-12:00, 16:00-18:00). Except for the days on which experiments were conducted, the animals were free access to drinking water. The animals were intraruminally infused every day prior to the morning feeding period with parotid saliva collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…As a result, their feed intake was 45.9% larger than that in non‐infusion treatment, and this increase in feed intake was observed during the first half of the feeding period. The increase in feed intake during the first half of the present experiment corresponds to the results of the experiment conducted by Sunagawa et al . (2002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, their feed intake was 45.9% larger than that in non‐infusion treatment, and this increase in feed intake was observed during the first half of the feeding period. The increase in feed intake during the first half of the present experiment corresponds to the results of the experiment conducted by Sunagawa et al . (2002).…”
Section: Discussionsupporting
confidence: 91%
“…The changes in eating rates in this experiment are similar to the results of experiments conducted by Prasetiyono et al . (2000) and Sunagawa et al . (2002) on goats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intraruminal infusions of hyper-osmotic NaCl, polyethylene glycol-400, sodium acetate, or sodium propionate increase rumen fluid osmolarity and decrease feed intake (Grovum 1995). On the other hand, when the ruminal fluid osmolality was decreased by the intraruminal infusion of an excessive amount of warm water (39.88C) in sheep fed alfalfa hay cubes, feed intake increased 30% (Sunagawa et al 2002). It is thought that the changes in ruminal fluid osmolarity are sensed by the osmoreceptors in the rumen wall and these signals are then transported to the central nervous system affecting feed intake (Leek and Harding 1975).…”
mentioning
confidence: 99%
“…When ruminants commence feeding on dry forage they secrete copious volumes of parotid saliva (Sato 1975;Sunagawa et al 2002Sunagawa et al , 2003, and large amounts of fluid and NaHCO 3 move from the circulating blood into the rumen in the form of saliva. Blair-West and Brook (1969) found that sheep fed lucerne chaff once a day showed a marked reduction in plasma volume within 15 min of the commencement of feeding.…”
mentioning
confidence: 99%